Disease activity, cytokines, chemokines and the risk of incident diabetes in rheumatoid arthritis. Issue 5 (4th January 2021) - Baker, Joshua F; England, Bryant R; George, Michael; Cannon, Grant; Sauer, Brian; Ogdie, Alexis; Hamilton, Bartlett C; Hunter, Carlos; Duryee, Michael J; Thiele, Geoffrey; Mikuls, Ted R
Abstract : Purpose: Rheumatoid arthritis (RA) is associated with a higher risk of diabetes mellitus (DM). Our aim was to determine associations between inflammatory disease activity (including evaluation of specific cytokines and chemokines) and incident DM. Methods: Participants were adults with physician-confirmed RA from Veteran's Affairs Rheumatoid Arthritis Registry. Disease activity and clinical assessments occur longitudinally as part of clinical care. Thirty cytokines and chemokines were measured in banked serum obtained at the time of enrolment. Cytokine/chemokine values were log-adjusted and standardised (per SD). Incident DM was defined based on validated algorithms using diagnostic codes and medications. Multivariable Cox proportional hazard models evaluated associations between clinical factors and incident DM. Independent associations between cytokines/chemokines and incident DM were assessed adjusting for age, sex, race, smoking, body mass index (BMI) and medication use at baseline. Results: Among 1866 patients with RA without prevalent DM at enrolment, there were 130 incident cases over 9223 person-years of follow-up. High Disease Activity Score (DAS28)-C reactive protein (CRP), obese BMI, older age and male sex were associated with greater risk for incident DM while current smoking and methotrexate use were protective. Patients using methotrexate were at lower risk. Several cytokines/chemokines evaluated were independently associated (per 1 SD) with DM incidence including interleukin(IL)-1, IL-6 and select macrophage-derived cytokines/chemokines (HR range 1.11–1.26). These associations were independent of the DAS28-CRP. Conclusions: Higher disease activity and elevated levels of cytokines/chemokines are associated with a higher risk of incident DM in patients with RA. Future study may help to determine if targeted treatments in at-risk individuals could prevent the development of DM.